Modified negative electrode sheet, preparation method, use and battery thereof

By using a modified polymer formed by in-situ polymerization of polymerizable monomers on the negative electrode sheet of the lithium-ion battery and forming a functional layer on its surface, the problem of insufficient mechanical strength and thermal stability of the existing modified negative electrode sheet is solved, and the safety performance of the lithium-ion battery is significantly improved.

CN115911268BActive Publication Date: 2025-02-28CHINA THREE GORGES CORPORATION +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211430620.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-15
Publication Date
2025-02-28
Estimated Expiration
2042-11-15

AI Technical Summary

Technical Problem

The mechanical strength of the existing modified negative electrode sheets is poor and the thermal stability still needs to be improved, resulting in insufficient safety of lithium-ion batteries in the case of thermal runaway.

Method used

A negative electrode material layer on the surface of the current collector contains a modified polymer formed by in situ polymerization of polymerizable monomers and forms a functional layer on its surface. The modified material includes a specific phosphonate part, a benzene ring part and an amide part to improve the thermal stability and mechanical strength of the polymer.

Benefits of technology

The thermal stability and mechanical strength of the modified negative electrode sheet are improved, and the safety performance of lithium-ion batteries in the early and middle stages of thermal runaway is enhanced, so as to avoid or delay the occurrence of thermal runaway.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure BDA0003944777480000021
    Figure BDA0003944777480000021
Patent Text Reader

Abstract

The present invention relates to the field of battery technology, and in particular to a modified negative electrode sheet and a preparation method, use and battery thereof. The negative electrode sheet comprises a current collector and a negative electrode material layer located on the surface of the current collector, wherein the negative electrode material layer contains a modified material, and / or the surface of the negative electrode material layer has a functional layer formed by the modified material, wherein the modified material comprises a polymer formed by in-situ polymerization of a polymerizable monomer, and the polymerizable monomer comprises a compound represented by formula (1): The polymer obtained by in-situ polymerization of the above-mentioned polymerizable monomer has good thermal stability, good mechanical strength and high cohesion, therefore, the modified negative electrode sheet of the present invention has good thermal stability and high mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a modified negative electrode sheet, a preparation method thereof, a use thereof, and a battery. Background Art

[0002] With the development of science and technology, lithium-ion batteries have been widely used in people's production and life, and the safety of lithium-ion batteries has attracted more and more attention. Thermal runaway is the main object of research on improving the safety of lithium-ion batteries.

[0003] Thermal runaway refers to a chain reaction phenomenon caused by various inducements. The large amount of heat and harmful gases emitted by thermal runaway can cause battery fire and explosion. Battery thermal runaway often starts with the decomposition of the negative electrode SEI film in the battery cell, followed by the reaction between the negative electrode and the electrolyte. The melting of the diaphragm triggers a strong redox reaction between the positive and negative electrodes. Then the positive electrode and the electrolyte will decompose, causing a large-scale internal short circuit, causing the electrolyte to burn, and then spread to other cells, causing serious thermal runaway, causing the entire battery pack to spontaneously combust or even explode. The triggering causes of thermal runaway can be divided into two categories: internal and external causes. Among them, internal causes refer to internal short circuits, and external causes include mechanical abuse, electrical abuse, and thermal abuse. Thermal runaway is usually divided into three stages: self-heating stage (50℃-140℃), thermal runaway stage (140℃-850℃), and thermal runaway termination stage (850℃-normal temperature).

[0004] Using polymers to perform composite modification on negative electrode sheets to form modified negative electrode sheets and improve the thermal stability of negative electrode sheets is one of the effective ways to improve the thermal runaway phenomenon of lithium-ion batteries and improve the safety of lithium-ion batteries. However, in the process of realizing the present invention, the inventors found that the mechanical strength of the modified negative electrode sheets in the prior art is poor, and their thermal stability still needs to be improved. Summary of the invention

[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the modified negative electrode sheet in the prior art that the mechanical strength is poor and the thermal stability still needs to be improved, thereby providing a modified negative electrode sheet and its preparation method, use and battery.

[0006] To this end, the present invention provides a modified negative electrode sheet, comprising a current collector and a negative electrode material layer located on the surface of the current collector, wherein the negative electrode material layer contains a modified material, and / or the surface of the negative electrode material layer has a functional layer formed by the modified material, wherein the modified material comprises a polymer formed by in-situ polymerization of a polymerizable monomer, and the polymerizable monomer comprises a compound represented by formula (1):

[0007]

[0008] Wherein, n is an integer of 1 to 10. Exemplarily, n may be 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10.

[0009] Optionally, at least one H on the alkyl, alkylene or alkenyl group in the compound represented by formula (1) is substituted by halogen.

[0010] Optionally, the polymerizable monomer includes a compound represented by formula (2):

[0011]

[0012] Among them, at least one of R1, R2, R3 and R4 is a halogen, and the rest are H.

[0013] Optionally, the relationship between the modified material and the negative electrode material layer may include any of the following situations:

[0014] 1) All modified materials are located inside the negative electrode material layer;

[0015] 2) Part of the modified material is located inside the negative electrode material layer, and part of the modified material is located on the surface of the negative electrode material layer and forms a functional layer;

[0016] 3) The modified materials are all located on the surface of the negative electrode material layer and form a functional layer.

[0017] Optionally, in the modified material located inside the negative electrode material layer, the polymer formed by in-situ polymerization of the polymerizable monomer is distributed in the gaps between the active particles of the negative electrode material in the form of a polymer network.

[0018] Optionally, based on the total weight of the negative electrode material and the modified material, the weight percentage of the polymer is 0.2-10%;

[0019] Optionally, the thickness of the functional layer is less than or equal to 10 μm.

[0020] Optionally, the negative electrode material may include a negative electrode active material, a negative electrode binder, a negative electrode conductive agent and other commonly used electrode additives. The negative electrode active material may be selected from any one of graphite, hard carbon, silicon, molybdenum disulfide, lithium titanate, graphene, silicon carbon, and silicon dioxide; the negative electrode binder may be selected from any one of styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylonitrile and polyacrylic acid; the negative electrode conductive agent may be selected from any one of Super-P, KS-6, carbon black, nano-carbon fiber, carbon nanotube, acetylene black or graphene.

[0021] Optionally, the modified material further comprises ceramic nanoparticles, and in the modified material, the weight ratio of the ceramic nanoparticles to the polymer is (0.1-10):1;

[0022] Optionally, the particle size D50 of the ceramic nanoparticles is 100 to 1000 nm;

[0023] Optionally, the ceramic nanoparticles include at least one of aluminum oxide ceramic nanoparticles, silicon oxide ceramic nanoparticles, titanium oxide ceramic nanoparticles, zinc oxide ceramic nanoparticles and boehmite ceramic nanoparticles.

[0024] The present invention also provides a method for preparing the modified negative electrode sheet as described in any one of the above, comprising the following steps:

[0025] Applying the negative electrode material slurry and the raw material emulsion for forming the modified material on the surface of the current collector to obtain a prefabricated negative electrode sheet;

[0026] heat treating the prefabricated negative electrode sheet;

[0027] The raw material emulsion for forming the modified material is mixed in the negative electrode material slurry, and / or the raw material emulsion for forming the modified material is coated on the surface of the negative electrode material layer formed by the negative electrode material slurry; the raw material emulsion for forming the modified material contains the polymerizable monomer.

[0028] Optionally, in the raw material emulsion for forming the modified material, the content of the polymerizable monomer is 0.5 to 50 wt %.

[0029] Optionally, the weight percentage of the polymerizable monomer is 0.2-10% based on the total weight of the non-solvent substance in the negative electrode material slurry and the non-solvent substance in the raw material emulsion forming the modified material. The non-solvent substance in the negative electrode material slurry can be, for example, a negative electrode active material, a negative electrode binder, a negative electrode conductive agent and other commonly used electrode additives; the non-solvent substance in the raw material emulsion forming the modified material can be, for example, a polymerizable monomer or a mixture of a polymerizable monomer and other auxiliary materials, and other auxiliary materials can be, for example, at least one of ceramic nanoparticles, initiators and emulsifiers.

[0030] Optionally, the raw material emulsion for forming the modified material further contains the ceramic nanoparticles, and the weight ratio of the ceramic nanoparticles to the polymerizable monomer is (0.1-10):1.

[0031] Optionally, the heat treatment conditions include: a temperature of 30 to 80° C. and a time of 1 to 24 hours. Preferably, the heat treatment conditions include: a temperature of 40 to 60° C. and a time of 10 to 15 hours.

[0032] Through the heat treatment, the polymerizable monomer is polymerized by heat initiation. The heat treatment method can be selected within a certain range. For example, the heat treatment can be heating plate baking, microwave baking, electromagnetic wave baking, and air blast drying.

[0033] Optionally, the raw material emulsion for forming the modified material further contains an initiator and an emulsifier, and the amount of the initiator is 0.1 to 5 parts by weight, and the amount of the emulsifier is 0.01 to 5 parts by weight relative to 100 parts by weight of the polymerizable monomer;

[0034] The initiator is selected from at least one of potassium persulfate, ammonium persulfate and hydrogen peroxide;

[0035] The emulsifier is selected from at least one of OP series emulsifiers, NP series emulsifiers, sodium dodecylbenzene sulfonate, N-dodecyldimethylamine, ethylene oxide and propylene oxide block copolymers. Exemplarily, the emulsifier may be OP-10 emulsifier and / or NP-10 emulsifier.

[0036] The present invention also provides use of any of the above-mentioned modified negative electrode sheets in preparing batteries.

[0037] The present invention also provides a battery, wherein the battery contains any one of the modified negative electrode sheets described above.

[0038] Optionally, the battery includes a liquid battery and / or a solid battery;

[0039] Optionally, the battery includes a liquid lithium secondary battery and / or a solid lithium secondary battery.

[0040] The technical solution of the present invention has the following advantages:

[0041] 1. The modified negative electrode sheet provided by the present invention comprises a current collector and a negative electrode material layer located on the surface of the current collector, wherein the negative electrode material layer contains a modified material, and / or the surface of the negative electrode material layer has a functional layer formed by the modified material, wherein the modified material comprises a polymer formed by in-situ polymerization of a polymerizable monomer, and the polymerizable monomer comprises a compound represented by formula (1). The polymerizable monomer comprises two phosphonate moieties, one benzene ring moiety and an amide moiety, wherein the phosphonate moiety has good flame retardant properties, thereby making the polymer have good thermal stability; the benzene ring moiety has rigidity, thereby making the polymer have good mechanical strength; the amide moiety contains hydrogen bonds, thereby making the polymer have high cohesion and mechanical strength. Therefore, the modified negative electrode sheet of the present invention has good thermal stability and high mechanical strength.

[0042] At the same time, the polymer monomer contains amide and ether oxygen bonds, so that the polymer contains polar group parts (amide and ether oxygen bonds), which have good lithium ion conduction function. Therefore, the modified negative electrode sheet of the present invention also has good lithium ion conduction function. That is, the modified negative electrode sheet of the present invention can have good thermal stability, high mechanical strength and good lithium ion conduction function, and can improve the safety performance of the battery without reducing the electrical performance of the battery. It has been proved by experiments that it can also improve the safety performance of the battery when it is overcharged.

[0043] In addition, the polar group contained in the polymer can homogenize the lithium ion flow, inhibit the lithium chromatography of the negative electrode material, and prevent the problem of SEI film instability caused by lithium chromatography. That is, the SEI thermal stability of the modified negative electrode sheet of the present invention is relatively high. The high thermal stability and good flame retardant properties enable the modified negative electrode sheet of the present invention to play a role in the early and middle stages of thermal runaway, avoid or delay the occurrence of thermal runaway, and is more conducive to improving the safety performance of the battery, especially the thermal runaway safety performance.

[0044] Furthermore, at least one H on the chain alkyl, chain alkylene or chain alkenyl in the polymerizable monomer can be substituted by halogen, which can further enhance the flame retardant properties of the polymer; the polymerizable monomer contains an unsaturated carbon-carbon bond at the terminal, which is beneficial to the polymerization of the polymerizable monomer and further beneficial to the formation of a uniform film; the polymer is obtained by in-situ polymerization of the polymerizable monomer, which is beneficial to the formation of a uniform polymer network or functional layer coating compared to non-in-situ polymerization.

[0045] 2. The modified negative electrode sheet provided by the present invention, the modified material also includes ceramic nanoparticles, a phosphonate part in the polymerizable monomer is located at the end group and is connected to an ethoxy group, the ethoxy group can generate hydroxyl groups through hydrolysis, and the hydroxyl groups can be riveted to the surface of the ceramic nanoparticles, so that the polymerizable monomer and the ceramic nanoparticles form a complex, which can further improve the electrochemical stability of the polymer.

[0046] 3. The method for preparing the modified negative electrode sheet provided by the present invention is compatible with the mainstream preparation process of lithium-ion battery electrode bodies, and the raw materials used are simple and easy to obtain, easy to scale up production, and suitable for large-scale application. DETAILED DESCRIPTION

[0047] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0048] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0049] (1) The negative electrode sheets involved in the embodiments and comparative examples of the present invention are as follows:

[0050] Graphite negative electrode sheet: Cu negative electrode current collector coated with negative electrode material, the thickness of the negative electrode material is 100 μm, and the negative electrode material includes 80wt% graphite, 10wt% negative electrode conductive agent (conductive carbon black), and 10wt% negative electrode binder (styrene-butadiene rubber + carboxymethyl cellulose; w / w, 2:1);

[0051] SiOC450 negative electrode sheet: Cu negative electrode current collector coated with negative electrode material, the thickness of the negative electrode material is 100μm, the negative electrode material includes SiOC450 80wt%, negative electrode conductive agent (conductive carbon black) 10wt%, negative electrode binder (styrene butadiene rubber + carboxymethyl cellulose; w / w, 2:1) 10wt%, wherein SiOC450 refers to SiO mixed graphite with a designed capacity of 450mAh / g.

[0052] (2) The polymerizable monomer M1 involved in the embodiment of the present invention is based on the structure shown in formula (1), n=1, and the specific structural formula is:

[0053]

[0054] The polymerizable monomer M2 is based on the structure shown in formula (2), n=2, R1, R2, R3 and R4 are all substituted with F, and the specific structural formula is:

[0055]

[0056] The polymerizable monomer M3, based on the structure shown in formula (1), has n=2 and a specific structural formula of:

[0057]

[0058] Preparation Example 1

[0059] The polymerizable monomer M1 is prepared as follows:

[0060] Under an argon atmosphere, 300 g of (2-carboxyethyl)phenylphosphoric acid and 200 g of diethyl hydroxymethyl phosphate were condensed, and the intermediate product A was separated and purified; 400 g of the intermediate product A and 200 g of isocyanoethyl methacrylate were added to 1000 g of dichloromethane, and 5 g of stannous octoate was added dropwise; the reaction was continued for 16 hours under an argon atmosphere at about 10°C, and the dichloromethane was removed by rotary evaporation to obtain a polymerizable monomer M1.

[0061] Preparation Example 2

[0062] The polymerizable monomer M2 is prepared as follows:

[0063] According to the method of Preparation Example 1, intermediate product A is prepared, and then 100g of intermediate product A and 100g of fluorinated 2-(2-methacryloyloxyethyloxy)ethyl isocyanate, i.e., fluorinated 2-(2-methacryloyloxyethoxy)ethyl isocyanate, are added to 1000g of dichloromethane under argon atmosphere, and 5g of stannous octoate is added dropwise; the reaction is continued for 16h under argon atmosphere at about 10°C, dichloromethane is removed by rotary evaporation, and polymerizable monomer M2 is obtained by separation and purification. The fluorination process can be carried out using perchloric acid fluoride, and the desired fluorinated 2-(2-methacryloyloxyethoxy)ethyl isocyanate is obtained by separation and purification.

[0064] Preparation Example 3

[0065] The polymerizable monomer M3 is prepared as follows:

[0066] The intermediate product A was prepared according to the method of Preparation Example 1, and then 100 g of the intermediate product A and 55 g of 2-(2-methacryloyloxyethyloxy)ethyl isocyanate were added to 1000 g of dichloromethane under an argon atmosphere, and 5 g of stannous octoate was added dropwise; the reaction was continued for 16 hours under an argon atmosphere at about 10° C., and the dichloromethane was removed by rotary evaporation to obtain a polymerizable monomer M3.

[0067] Example 1

[0068] The modified negative electrode sheet was prepared according to the following steps:

[0069] (1) 100 g of polymerizable monomer M1 and 0.5 g of initiator (potassium persulfate) were dissolved in water, and 0.1 g of emulsifier (OP-10) was added to prepare an aqueous emulsion with a mass fraction of polymerizable monomer M1 of 2%, thereby obtaining a raw material emulsion for forming a modified material;

[0070] (2) taking an appropriate amount of the raw material emulsion for forming the modified material obtained in step (1) and coating it on the surface of the graphite negative electrode sheet, so that the weight percentage of the polymerizable monomer M1 is 2% based on the total weight of the negative electrode material and the non-solvent substance in the raw material emulsion for forming the modified material;

[0071] (3) The graphite negative electrode sheet coated with the raw material emulsion for forming the modified material is baked to polymerize the polymerizable monomer M1 in situ to form the modified material, thereby obtaining a modified negative electrode sheet, wherein the baking temperature is 50° C. and the baking time is 12 hours.

[0072] In the modified negative electrode sheet prepared in this embodiment, the modified material is a polymer formed by in-situ polymerization of the polymerizable monomer M1, and the weight of the polymer accounts for 2% of the total weight of the negative electrode material and the modified material. Due to the emulsion coating, a part of the modified material penetrates into the surface layer of the negative electrode material layer, and the remaining part of the modified material covers the surface of the negative electrode material layer to form a functional layer, and the thickness of the functional layer is 100nm.

[0073] Example 2

[0074] The modified negative electrode sheet was prepared according to the following steps:

[0075] (1) dissolving 100 g of polymerizable monomer M2, 100 g of alumina ceramic nanoparticles (D50=300 nm) and 1 g of initiator (potassium persulfate) in water, adding 0.1 g of emulsifier (OP-10) to prepare an aqueous emulsion with a mass fraction of polymerizable monomer M2 of 5%, thereby obtaining a raw material emulsion for forming a modified material;

[0076] (2) taking an appropriate amount of the raw material emulsion for forming the modified material obtained in step (1) and coating it on the surface of the SiOC450 negative electrode sheet, so that the weight percentage of the polymerizable monomer M2 is 5% based on the total weight of the negative electrode material and the non-solvent substance in the raw material emulsion for forming the modified material;

[0077] (3) The SiOC450 negative electrode sheet coated with the raw material emulsion for forming the modified material is baked to polymerize the polymerizable monomer M2 in situ to form the modified material, thereby obtaining a modified negative electrode sheet, wherein the baking temperature is 50° C. and the baking time is 12 hours.

[0078] In the modified negative electrode sheet prepared in this embodiment, the modified material is a composite formed by the polymer formed by in-situ polymerization of the polymerizable monomer M2 and the alumina ceramic nanoparticles, the weight ratio of the alumina ceramic nanoparticles to the polymer is 1:1, and the weight of the polymer accounts for 5% of the total weight of the negative electrode material and the modified material. Due to the emulsion coating, a part of the modified material penetrates into the surface layer of the negative electrode material layer, and the remaining part of the modified material covers the surface of the negative electrode material layer to form a functional layer, and the thickness of the functional layer is 500nm.

[0079] Example 3

[0080] The modified negative electrode sheet was prepared according to the following steps:

[0081] (1) 100 g of polymerizable monomer M3, 10 g of silicon oxide ceramic nanoparticles (D50=400 nm) and 1 g of initiator (potassium persulfate) were dissolved in water, and 0.2 g of emulsifier (OP-10) was added to prepare an aqueous emulsion with a mass fraction of polymerizable monomer M3 of 10%, thereby obtaining a raw material emulsion for forming a modified material;

[0082] (2) 80 kg of SiOC450, 10 kg of negative electrode conductive agent (conductive carbon black), and 10 kg of negative electrode binder (styrene-butadiene rubber + carboxymethyl cellulose; w / w, 2:1) were added with water to prepare a SiOC450 negative electrode material slurry with a solid content of 40%;

[0083] (3) Take appropriate amounts of the raw material emulsion for forming the modified material obtained in step (1) and the SiOC450 negative electrode material slurry obtained in step (2), and mix them evenly so that the weight percentage of the polymerizable monomer M3 is 10% based on the total weight of the non-solvent substance in the SiOC450 negative electrode material slurry and the non-solvent substance in the raw material emulsion for forming the modified material;

[0084] (4) coating the mixed slurry obtained in step (3) on the surface of the Cu negative electrode current collector with a coating thickness of 100 μm;

[0085] (5) The Cu negative electrode current collector coated with the mixed slurry is baked to polymerize the polymerizable monomer M3 in situ to form a modified material, thereby obtaining a modified negative electrode sheet, wherein the baking temperature is 50° C. and the baking time is 12 hours.

[0086] In the modified negative electrode sheet prepared in this embodiment, the modified material is a composite formed by a polymer formed by in-situ polymerization of the polymerizable monomer M3 and silicon oxide ceramic nanoparticles, the weight ratio of silicon oxide ceramic nanoparticles to the polymer is 0.1:1, and the weight of the polymer accounts for 10% of the total weight of the negative electrode material and the modified material. The modified material is evenly distributed in the negative electrode material layer.

[0087] Example 4

[0088] A modified negative electrode sheet is prepared according to the method of Example 1, except that step (2) is replaced by: taking an appropriate amount of the raw material emulsion for forming the modified material obtained in step (1) and coating it on the surface of the graphite negative electrode sheet, so that the weight percentage of the polymerizable monomer M1 is 0.2% based on the total weight of the negative electrode material and the non-solvent substance in the raw material emulsion for forming the modified material.

[0089] In the modified negative electrode sheet prepared in this embodiment, the modified material is a polymer formed by in-situ polymerization of the polymerizable monomer M1, and the weight of the polymer accounts for 0.2% of the total weight of the negative electrode material and the modified material. Due to the emulsion coating, a part of the modified material penetrates into the surface layer of the negative electrode material layer, and the remaining part of the modified material covers the surface of the negative electrode material layer to form a functional layer, and the thickness of the functional layer is less than 50nm.

[0090] Example 5

[0091] A modified negative electrode sheet was prepared according to the method of Example 1, except that step (2) was replaced by: taking an appropriate amount of the raw material emulsion for forming the modified material obtained in step (1) and coating it on the surface of the graphite negative electrode sheet, so that the weight percentage of the polymerizable monomer M1 was 10% based on the total weight of the negative electrode material and the non-solvent substance in the raw material emulsion for forming the modified material.

[0092] In the modified negative electrode sheet prepared in this embodiment, the modified material is a polymer formed by in-situ polymerization of the polymerizable monomer M1, and the weight of the polymer accounts for 10% of the total weight of the negative electrode material and the modified material. Due to the emulsion coating, a part of the modified material penetrates into the surface layer of the negative electrode material layer, and the remaining part of the modified material covers the surface of the negative electrode material layer to form a functional layer, and the thickness of the functional layer is 1000nm.

[0093] Example 6

[0094] The modified negative electrode sheet was prepared according to the method of Example 2, except that in step (1), the amount of alumina ceramic nanoparticles (D50=300nm) used was 10g.

[0095] In the modified negative electrode sheet prepared in this embodiment, the modified material is a composite formed by the polymer formed by in-situ polymerization of the polymerizable monomer M2 and the alumina ceramic nanoparticles, the weight ratio of the alumina ceramic nanoparticles to the polymer is 0.1:1, and the weight of the polymer accounts for 5% of the total weight of the negative electrode material and the modified material. Due to the emulsion coating, a part of the modified material penetrates into the surface layer of the negative electrode material layer, and the remaining part of the modified material covers the surface of the negative electrode material layer to form a functional layer, and the thickness of the functional layer is 300nm.

[0096] Example 7

[0097] The modified negative electrode sheet was prepared according to the method of Example 2, except that in step (1), the amount of alumina ceramic nanoparticles (D50=300 nm) used was 1000 g.

[0098] In the modified negative electrode sheet prepared in this embodiment, the modified material is a composite formed by the polymer formed by in-situ polymerization of the polymerizable monomer M2 and the alumina ceramic nanoparticles, the weight ratio of the alumina ceramic nanoparticles to the polymer is 10:1, and the weight of the polymer accounts for 5% of the total weight of the negative electrode material and the modified material. Due to the emulsion coating, a part of the modified material penetrates into the surface layer of the negative electrode material layer, and the remaining part of the modified material covers the surface of the negative electrode material layer to form a functional layer, and the thickness of the functional layer is 700nm.

[0099] Example 8

[0100] The modified negative electrode sheet was prepared according to the method of Example 3, except that the amount of silicon oxide ceramic nanoparticles (D50=400 nm) used in step (1) was 1000 g.

[0101] In the modified negative electrode sheet prepared in this embodiment, the modified material is a composite formed by a polymer formed by in-situ polymerization of the polymerizable monomer M3 and silicon oxide ceramic nanoparticles, the weight ratio of silicon oxide ceramic nanoparticles to the polymer is 10:1, and the weight of the polymer accounts for 10% of the total weight of the negative electrode material and the modified material. The modified material is evenly distributed in the negative electrode material layer.

[0102] Example 9

[0103] The modified negative electrode sheet was prepared according to the method of Example 2, except that in operation (3) of this example, the baking temperature was 30° C. and the baking time was 24 hours.

[0104] Example 10

[0105] The modified negative electrode sheet was prepared according to the method of Example 2, except that in operation (3) of this example, the baking temperature was 80° C. and the baking time was 1 hour.

[0106] Comparative Example 1

[0107] Prepare polymerizable monomer D1, the preparation method is as follows:

[0108]

[0109] Under an argon atmosphere, 250 g of (2-carboxyethyl)phosphoric acid and 200 g of diethyl hydroxymethyl phosphate were condensed, and the intermediate product B was separated and purified; 350 g of the intermediate product B and 200 g of isocyanoethyl methacrylate were added to 1000 g of dichloromethane, and 5 g of stannous octoate was added dropwise; the reaction was continued for 16 hours under an argon atmosphere at about 10°C, and the dichloromethane was removed by rotary evaporation to obtain a polymerizable monomer D1.

[0110] A modified negative electrode sheet was prepared according to the method of Example 1, except that the polymerizable monomer M1 was replaced by an equal weight of polymerizable monomer D1.

[0111] Comparative Example 2

[0112] Prepare polymerizable monomer D2, the preparation method is as follows:

[0113]

[0114] Under argon atmosphere, 250 g of (2-carboxyethyl)phenylphosphoric acid and 200 g of isocyanoethyl methacrylate were added to 1000 g of dichloromethane, and 5 g of stannous octoate was added dropwise; the reaction was continued for 16 h under argon atmosphere at about 10° C., and dichloromethane was removed by rotary evaporation to obtain polymerizable monomer D2.

[0115] A modified negative electrode sheet was prepared according to the method of Example 1, except that the polymerizable monomer M1 was replaced by an equal weight of polymerizable monomer D2.

[0116] Comparative Example 3

[0117] Prepare polymerizable monomer D3, the preparation method is as follows:

[0118]

[0119] Under an argon atmosphere, 250 g of (2-carboxyethyl)phenylphosphoric acid and 180 g of (dimethylphosphinyl)methanol are condensed, and the intermediate product C is separated and purified; 300 g of the intermediate product C and 200 g of isocyanoethyl methacrylate are added to 1000 g of dichloromethane, and 5 g of stannous octoate is added dropwise; the reaction is continued for 16 hours under an argon atmosphere at about 10°C, and the dichloromethane is removed by rotary evaporation to obtain a polymerizable monomer D3.

[0120] A modified negative electrode sheet was prepared according to the method of Example 2, except that the polymerizable monomer M2 was replaced by an equal weight of polymerizable monomer D3.

[0121] Comparative Example 4

[0122] A modified negative electrode sheet was prepared according to the method of Example 1, except that an equal weight of PVDF was used to replace the polymerizable monomer M1.

[0123] Experimental example

[0124] The modified negative electrode sheets prepared in Examples 1-10 and Comparative Examples 1-4 were used to prepare secondary lithium batteries, and the preparation methods were as follows:

[0125] The positive electrode material (NCM (S85E) 80wt%, positive electrode conductive agent SuperP 10wt%, positive electrode adhesive PVDF 10wt%) was coated on the surface of the Al positive electrode current collector to prepare a positive electrode sheet, and the modified negative electrode sheets prepared in Examples 1-10 and Comparative Examples 1-4 were respectively used, LiPF6 (1M) -EC / DMC (v / v, 3: 7) was used as the electrolyte, and PE was used as the separator. The secondary lithium batteries were assembled according to the conventional methods in the art, and after the conventional processing steps in the art such as liquid injection, formation, and capacity separation, electrochemical tests and safety performance tests were carried out respectively.

[0126] A secondary lithium battery was prepared using the same method using an unmodified graphite negative electrode sheet as a control battery.

[0127] (1) Battery charge and discharge performance test

[0128] The secondary lithium battery prepared above was charged to 4.25V at a constant current of 0.1C at room temperature, and then discharged to 3V at a constant current of 0.1C, and the first discharge capacity and first charge capacity of the battery were recorded, and the first charge and discharge efficiency (%) was calculated as first discharge capacity / first charge capacity×100%. The test results are shown in Table 1.

[0129] Table 1 Battery charge and discharge performance test results

[0130]

[0131]

[0132] (2) Battery cycle performance test

[0133] The secondary lithium battery prepared above was charged to 4.25V at 1C constant current and constant voltage at room temperature, with a charge cutoff current of 0.05C, and then discharged to 3V at 1C constant current, and the first charge capacity and discharge capacity were recorded, and the discharge efficiency (%) was calculated; after repeated charge and discharge cycles for 100, 200 and 300 times, the discharge capacity of the 100th, 200th and 300th cycles was recorded and the capacity retention rate after the cycle was calculated, where the capacity retention rate after n cycles (%) = discharge capacity of the nth time / first discharge capacity × 100%; the cutoff voltage was 4.95V. The test results are shown in Table 2.

[0134] Table 2 Battery cycle performance test results

[0135]

[0136] (3) Hot box pass rate test

[0137] The secondary lithium battery prepared above was subjected to a hot box pass rate test according to the following method, and the test results are shown in Table 3:

[0138] a) At 23℃±2℃, charge at a constant current of 1C until the charge termination voltage is reached, then switch to constant voltage charging until the charge current rate drops to 0.05C, stop charging, and let stand for 1h;

[0139] b) Place the battery in a test chamber and heat the chamber at a rate of 5°C / min. When the temperature inside the chamber reaches 160°C±2°C, keep the temperature constant for 1 hour.

[0140] The battery passes if it does not emit smoke, catch fire or explode, otherwise it fails.

[0141] (4) Heavy object impact pass rate test

[0142] The secondary lithium battery prepared above was subjected to a heavy object impact pass rate test according to the following method, and the test results are shown in Table 3:

[0143] a) At 23℃±2℃, charge at a constant current of 1C until the charge termination voltage is reached, then switch to constant voltage charging until the charge current rate drops to 0.05C, stop charging, and let stand for 1h;

[0144] b) Place the battery on the platform surface, place a metal rod with a diameter of 15.8mm±0.2mm horizontally on the upper surface of the geometric center of the battery, use a weight with a mass of 9.1kg±0.1kg to hit the battery surface with the metal rod in a free fall state from a height of 610mm±25mm, and observe for 6h.

[0145] It is required that soft-pack batteries only undergo impact tests on the wide surface, and one sample only undergoes one impact test;

[0146] The battery passes if it does not emit smoke, catch fire or explode, otherwise it fails.

[0147] (5) Acupuncture pass rate test

[0148] The secondary lithium battery prepared above was subjected to a needle penetration test according to the following method. The test results are shown in Table 3:

[0149] a) At 23℃±2℃, charge at a constant current of 1C until the charge termination voltage is reached, then switch to constant voltage charging until the charge current rate drops to 0.05C, stop charging, and let stand for 1h;

[0150] b) Use A high temperature resistant steel needle (the cone angle of the needle tip is 45°, the surface of the needle is smooth, without rust, oxide layer and oil stain) is inserted perpendicular to the battery plate at a speed of 25 mm / s. The penetration position is the geometric center of the pierced surface, and the steel needle stays in the battery.

[0151] c) Observe for 1 hour;

[0152] The battery passes if it does not emit smoke, catch fire or explode, otherwise it fails.

[0153] Table 3 Battery safety performance test results

[0154] Battery ID Hot box pass rate Heavy object impact passing rate Acupuncture pass rate Example 1 3 / 5 4 / 5 2 / 5 Example 2 4 / 5 4 / 5 3 / 5 Example 3 3 / 5 4 / 5 2 / 5 Example 4 2 / 5 3 / 5 1 / 5 Example 5 4 / 5 4 / 5 2 / 5 Example 6 3 / 5 3 / 5 2 / 5 Example 7 3 / 5 4 / 5 2 / 5 Example 8 2 / 5 3 / 5 1 / 5 Example 9 2 / 5 3 / 5 1 / 5 Example 10 2 / 5 3 / 5 1 / 5 Comparative Example 1 1 / 5 3 / 5 1 / 5 Comparative Example 2 1 / 5 2 / 5 1 / 5 Comparative Example 3 1 / 5 1 / 5 0 / 5 Comparative Example 4 1 / 5 1 / 5 0 / 5 Control battery 1 / 5 1 / 5 0 / 5

[0155] Among them, n / 5 means that n samples out of 5 secondary lithium battery samples passed the test.

[0156] (6) Verification of overcharge prevention effect

[0157] Test the overcharge voltage of each secondary lithium battery as follows:

[0158] a) At 23℃±2℃, charge at a constant current of 1C until the charge termination voltage is reached, then switch to constant voltage charging until the charge current rate drops to 0.05C, stop charging, and let stand for 1h;

[0159] b) Continuously charge at a constant current of 1C until the battery experiences thermal runaway. Record the battery voltage when thermal runaway begins, which is the overcharge voltage of the corresponding secondary lithium battery.

[0160] Table 4 Battery overcharge voltage test results

[0161]

[0162]

[0163] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A modified negative electrode sheet, comprising a current collector and a negative electrode material layer located on the surface of the current collector, characterized in that: The negative electrode material layer contains a modified material, and / or the surface of the negative electrode material layer has a functional layer formed by the modified material, the modified material includes a polymer formed by in-situ polymerization of a polymerizable monomer, and the polymerizable monomer includes a compound represented by formula (1): Formula (1), Here, n is an integer from 1 to 10.

2. The modified negative electrode sheet according to claim 1, characterized in that: In the compound represented by formula (1), at least one H on the alkyl, alkylene or alkenyl group is substituted with halogen.

3. The modified negative electrode sheet according to claim 2, characterized in that: The polymerizable monomer includes a compound represented by formula (2): Formula (2), Among them, at least one of R1, R2, R3 and R4 is a halogen, and the rest are H.

4. The modified negative electrode sheet according to any one of claims 1 to 3, characterized in that: Based on the total weight of the negative electrode material and the modified material, the weight percentage of the polymer is 0.2-10%.

5. The modified negative electrode sheet according to claim 4, characterized in that: The thickness of the functional layer is less than or equal to 10 μm.

6. The modified negative electrode sheet according to any one of claims 1 to 3, characterized in that: The modified material further comprises ceramic nanoparticles. In the modified material, the weight ratio of the ceramic nanoparticles to the polymer is (0.1-10):

1.

7. The modified negative electrode sheet according to claim 6, characterized in that: The particle size D50 of the ceramic nanoparticles is 100-1000 nm.

8. The modified negative electrode sheet according to claim 6, characterized in that: The ceramic nanoparticles include at least one of aluminum oxide ceramic nanoparticles, silicon oxide ceramic nanoparticles, titanium oxide ceramic nanoparticles, zinc oxide ceramic nanoparticles and boehmite ceramic nanoparticles.

9. A method for preparing a modified negative electrode sheet according to any one of claims 1 to 8, characterized in that: The steps include: Applying the negative electrode material slurry and the raw material emulsion for forming the modified material on the surface of the current collector to obtain a prefabricated negative electrode sheet; heat treating the prefabricated negative electrode sheet; The raw material emulsion for forming the modified material is mixed in the negative electrode material slurry, and / or the raw material emulsion for forming the modified material is coated on the surface of the negative electrode material layer formed by the negative electrode material slurry; the raw material emulsion for forming the modified material contains the polymerizable monomer.

10. The preparation method according to claim 9, characterized in that: In the raw material emulsion for forming the modified material, the content of the polymerizable monomer is 0.5 to 50 wt %.

11. The preparation method according to claim 9, characterized in that: The raw material emulsion for forming the modified material also contains ceramic nanoparticles, and the weight ratio of the ceramic nanoparticles to the polymerizable monomer is (0.1-10):

1.

12. The preparation method according to claim 9, characterized in that: The heat treatment conditions include: temperature of 30 to 80° C. and time of 1 to 24 hours.

13. The preparation method according to any one of claims 9 to 12, characterized in that The raw material emulsion for forming the modified material further contains an initiator and an emulsifier. Relative to 100 parts by weight of the polymerizable monomer, the amount of the initiator is 0.1 to 5 parts by weight, and the amount of the emulsifier is 0.01 to 5 parts by weight. The initiator is selected from at least one of potassium persulfate, ammonium persulfate and hydrogen peroxide; The emulsifier is selected from at least one of OP series emulsifiers, NP series emulsifiers, sodium dodecylbenzene sulfonate, N-dodecyldimethylamine, ethylene oxide and propylene oxide block copolymers.

14. Use of the modified negative electrode sheet according to any one of claims 1 to 8 in preparing a battery.

15. A battery, characterized in that: The battery contains the modified negative electrode sheet according to any one of claims 1 to 8.

16. The battery according to claim 15, characterized in that The battery is a liquid battery or a solid battery.

17. The battery according to claim 16, characterized in that The battery is a liquid lithium secondary battery or a solid lithium secondary battery.

Citation Information

Patent Citations

  • Modified electrode body, preparation method and application thereof and lithium ion battery

    CN114883570A

  • Flame-retardant high-elasticity polymer for lithium metal protection, lithium secondary battery and manufacturing method

    US20220255080A1